Impact of Stress on Employees Performances: A Case Study on Pubali Bank Limited - Nazmul, Abdul K.; Hassan, Farheen; Hossain, Md. M. (AIUB Journal of Business and Economics, 2019)
This paper explores the factors responsible for stressful work environment in Pubali bank, Bangladesh as a case study and suggests measures to overcome the negative impacts of stress for employees in the organization. This study uses a multilinear regression analysis based on questionnaire surveys among 40 randomly selected employees of Pubali bank. Data was collected from the employees working in the corporate branch and head office located in Motijheel, Dhaka. The findings suggest ineffective management system affects increased absenteeism, increased employee turnover, reduced productivity, and reduction in organizational overall efficiency. Lack of health and safety arrangements elucidate employees to become physically and mentally imbalanced. Lack of health and safety arrangements also elucidates organizational overall efficiency to be reduced. In addition, dissatisfying reward system introduces increased employee complaints and job insecurity, bringing increased organizational conflicts.